Multidisciplinary prospective study of mother-to-child chikungunya virus infections on the island of La Réunion. - Patrick Gérardin; Georges Barau; Alain Michault; Marc Bintner; Hanitra Randrianaivo; Ghassan Choker; Yann Lenglet; Yasmina Touret; Anne Bouveret; Philippe Grivard; Karin Le Roux; Séverine Blanc; et al. (PLoS Medicine, 2008)
Background An outbreak of chikungunya virus affected over one-third of the population of La Réunion Island between March 2005 and December 2006. In June 2005, we identified the first case of mother-to-child chikungunya virus transmission at the Groupe Hospitalier Sud-Réunion level-3 maternity department. The goal of this prospective study was to characterize the epidemiological, clinical, biological, and radiological features and outcomes of all the cases of vertically transmitted chikungunya infections recorded at our institution during this outbreak. Methods and findings Over 22 mo, 7,504 women delivered 7,629 viable neonates; 678 (9.0%) of these parturient women were infected (positive RT-PCR or IgM serology) during antepartum, and 61 (0.8%) in pre- or intrapartum. With the exception of three early fetal deaths, vertical transmission was exclusively observed in near-term deliveries (median duration of gestation: 38 wk, range 35-40 wk) in the context of intrapartum viremia (19 cases of vertical transmission out of 39 women with intrapartum viremia, prevalence rate 0.25%, vertical transmission rate 48.7%). Cesarean section had no protective effect on transmission. All infected neonates were asymptomatic at birth, and median onset of neonatal disease was 4 d (range 3-7 d). Pain, prostration, and fever were present in 100% of cases and thrombocytopenia in 89%. Severe illness was observed in ten cases (52.6%) and mainly consisted of encephalopathy (n = 9; 90%). These nine children had pathologic MRI findings (brain swelling, n = 9; cerebral hemorrhages, n = 2), and four evolved towards persistent disabilities. Conclusions Mother-to-child chikungunya virus transmission is frequent in the context of intrapartum maternal viremia, and often leads to severe neonatal infection. Chikungunya represents a substantial risk for neonates born to viremic parturients that should be taken into account by clinicians and public health authorities in the event of a chikungunya outbreak.